2019
DOI: 10.1038/s41598-019-56226-z
|View full text |Cite
|
Sign up to set email alerts
|

Habitual physical activity mediates the acute exercise-induced modulation of anxiety-related amygdala functional connectivity

Abstract: Aerobic exercise, in relation to physical activity, has been shown to have beneficial effects on anxiety. However, the underlyig neural mechanism remains elusive. Using a within-subject crossover design, this fMRI study examined how exercise (12-min treadmill running versus walking) mediated amygdala reactivity to explicit and implicit (backward masked) perception of emotional faces in young adults (N = 40). Results showed that acute exercise-induced differences of state anxiety (STAI-S) varied as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 61 publications
(69 reference statements)
2
28
0
3
Order By: Relevance
“…We found that higher fit participants experienced greater improvements in mood following the aerobic exercise. This accords with previous studies reporting that better fitness level [50] and regular exercise participation are associated with more positive affective responses [5153] and enhanced anxiety relief [52,54] following a bout of exercise. Antinociceptive effects of acute exercise have also been found to depend on fitness level [55].…”
Section: Discussionsupporting
confidence: 92%
“…We found that higher fit participants experienced greater improvements in mood following the aerobic exercise. This accords with previous studies reporting that better fitness level [50] and regular exercise participation are associated with more positive affective responses [5153] and enhanced anxiety relief [52,54] following a bout of exercise. Antinociceptive effects of acute exercise have also been found to depend on fitness level [55].…”
Section: Discussionsupporting
confidence: 92%
“…( 29 ) found higher odds for women than for men as regards inverse associations of PA with changes in perceived anxiety; such gender differences might be because both contextual and cultural differences contribute to influencing anxiety ( 30 , 31 ). Other differences among subgroups could result from the habits of performing PA, since previous studies have indicated a mediator effect of usual exposure to PA over acute anxiety responses ( 32 ). Also, the type of PA might play an important role in this association, since recent research has emphasized the effects of specific physical exercise such as high interval intensity training (HIIT) on mental health, showing higher improvements than moderate-intensity continuous training in individuals experiencing mental disorders ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a significant body of work has observed improvements in mood state associated with higher levels of PA ( 34 , 35 ). Furthermore, not only were healthy populations that showed mood enhancement, but also populations with previous conditions ( 32 , 36 ); even short bouts of PA have been observed to improve mood in older adults ( 37 ). Particularly, the acute responses to low-intensity aerobic exercise were those that enhanced mood the most in young women when compared with responses to high-intensity aerobic exercise ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, six studies did not perform neuroimaging using fMRI [80][81][82] or applied other neuroimaging techniques (e.g., functional near-infrared spectroscopy) [83][84][85]. The remaining 10 studies did not perform cognitive testing [86][87][88][89][90][91][92][93][94] or did not report data because they describe a study protocol [95].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%